2002
DOI: 10.1001/archderm.138.8.1019
|View full text |Cite
|
Sign up to set email alerts
|

Correlations Between Clinical Patterns and Causes of Erythema Multiforme Majus, Stevens-Johnson Syndrome, and Toxic Epidermal Necrolysis

Abstract: Background: It was proposed that Stevens-Johnson syndrome and toxic epidermal necrolysis differed from erythema multiforme majus by the pattern and localization of skin lesions. Objective: To evaluate the validity of this clinical separation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
406
2
42

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 551 publications
(463 citation statements)
references
References 21 publications
8
406
2
42
Order By: Relevance
“…4,12 They found that SJS is usually related to drugs, whereas EM major is most commonly secondary to herpes simplex virus infection. 4,12 Our data support these findings, with 20 cases secondary to the use of medications, whereas no patient had a documented herpes simplex virus infection. In our patients with drug-induced SJS, the mean interval between drug administration and onset of cutaneous findings was 15.3 days.…”
Section: Discussionmentioning
confidence: 99%
“…4,12 They found that SJS is usually related to drugs, whereas EM major is most commonly secondary to herpes simplex virus infection. 4,12 Our data support these findings, with 20 cases secondary to the use of medications, whereas no patient had a documented herpes simplex virus infection. In our patients with drug-induced SJS, the mean interval between drug administration and onset of cutaneous findings was 15.3 days.…”
Section: Discussionmentioning
confidence: 99%
“…Rumień wielopostaciowy, zespół Stevensa-Johnsona oraz toksyczna nekroliza naskórka są ostrymi chorobami przebiegającymi z zajęciem skóry i błon śluzowych, wywoływanymi zakażeniem lub przyjmowaniem niektórych leków [1]. Reakcje skórne występujące w związ-ku z radioterapią są powszechnie znanym zjawiskiem.…”
Section: Wprowadzenieunclassified
“…Erythema multiforme, Stevens-Johnson syndrome and toxic epidermal necrolysis are acute mucocutaneous disorders which can be induced by infections or drugs [1]. Cutaneous reactions triggered by radiation therapy are a well-recognized phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…A SJS és a TEN ugyanazon folyamat különbö-zô súlyosságú formái (a SJS a TEN minor formájának mondható), míg az EEM egy külön kórkép. Ez a csoportosítás Bastuji-Garin és társainak 1993-as tanulmányán alapul (1,2,5,6,7). Az irodalmi adatok alátámasztják, hogy gyógyszer provokáció elsôsorban a SJS/TEN hátte-rében feltételezhetô, míg az EEM etiológiájáért nagyobbrészt a kórokozók egyre szélesedô köre tehetô felelôssé.…”
Section: áBra 77 éVes Sjs-s Férfibeteg Ajkán Vaskos Pörkkel Fedett Erunclassified
“…Korábbi tanulmányok szerint az EEM, a SJS, és a TEN bármely életkorban kialakulhat, az EEM elsôsorban a fiatal felnôtteket érinti, a SJS és a TEN az idôsebbeket veszélyezteti, a megjelenés kockázata a negyedik évtizedtôl megnô (2,5,7). Saját vizsgálataink során az EEM-s betegek átlagéletkorát (41,1 év) ezen irodalmi adatoknak megfelelônek találtuk, a SJS betegek átlagéletkora az EEM-s betegekénél valamivel alacsonyabb volt (37,3 év), így ez eltért az irodalmi adatoktól.…”
Section: Megbeszélésunclassified